The Role of the City in Fostering Intergroup Communication in a Multicultural Environment: Saint-Petersburg's Case - Natalya V. Taranova (Fondazione Eni Enrico Mattei (FEEM), 2003)
In this paper two aspects of the issue will be discussed. First, there is the role of authorities, NGOs in forming the multicultural environment in the city with cultural diversity. Second, the city as social context, the images and myths of the city determine discourse on multiculturalism and influence the cross-cultural communication in the city. After describing historically shaped images of the city, employment of city's myths and symbols in discourse and policy of multiculturalism, and role of city's institutions in fostering inter-group communication, this paper will discuss the inclusive culture of the city, shaped by the networking interaction, which blurs the distinction between «insiders» and «outsiders». Here the trends of (post)modern inter/trans-national relations will be extrapolated on the trans-cultural interaction in the multicultural city, taking into consideration that network interactions build up not between the territories, but in the space, where logic of borders overcomes.
Keywords: Z10; 330; Multicultural; Identity; Image; Myth; Discourse; We-groups; Inclusive networks; Inclusive culture; Transnational interaction; Transnational civil society